Craft and Sustainability: Potential for Design Intervention in Crafts in the Yangtze River Delta, China. (28th July 2017) - Zhan, Xiaofang; Walker, Stuart; Hernandez-Pardo, Ricardo; Evans, Martyn
Abstract: Modern manufacturing for global markets tends to homogenize material culture through its centralized production and divisive production process. In contrast, craft practices usually have a strong local identity through their application of holistic making practices, context-based knowledge, culturally specific responses and community-centred production. This form of locally-based, customizable and responsive production is discussed here in terms of its relationship to sustainability and as a promising direction for future manufacturing. Despite the potentially strong relationship between craft and sustainability, there is still only limited research exploring this relationship and how craft can more effectively contribute to contemporary industry and life in general. This paper begins by developing an understanding of the relationship between craft and sustainability. From this, we identify: 1) barriers to craft's development for sustainability, and 2) potential directions to which design can contribute. We then provide an analysis of the current state of crafts in the Yangtze River Delta (YRD) and identify the challenges and potential for design interventions in this region.